2015
DOI: 10.1016/j.cub.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Fas-Activated Mitochondrial Apoptosis Culls Stalled Embryonic Stem Cells to Promote Differentiation

Abstract: SUMMARY The intrinsic (mitochondrial) apoptotic pathway is a conserved cell death program crucial for eliminating superfluous, damaged, or incorrectly specified cells [1], and the multi-domain pro-death BCL-2 family proteins BAX and BAK are required for its activation [2, 3]. In response to internal damage or developmental signals, BAX and/or BAK permeabilize the mitochondrial outer membrane [4, 5], resulting in cytochrome c release and activation of effector caspases such as Caspase-3 (Casp3) [6]. While the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…To further assess the pluripotency of colonies generated from Bak −/− ; Bax −/− MEFs, we cultured them over at least five passages to confirm their self-renewal capacity, during which time they maintained a shiny, rounded morphology and expression of the pluripotency markers SSEA1, NANOG, and OCT4 ( Figure 1 C). These observations are consistent with those reported for embryonic stem cells deficient in BAK and BAX ( Wang et al., 2015 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To further assess the pluripotency of colonies generated from Bak −/− ; Bax −/− MEFs, we cultured them over at least five passages to confirm their self-renewal capacity, during which time they maintained a shiny, rounded morphology and expression of the pluripotency markers SSEA1, NANOG, and OCT4 ( Figure 1 C). These observations are consistent with those reported for embryonic stem cells deficient in BAK and BAX ( Wang et al., 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, using low pass whole genome sequencing, we observed no significant difference in the number of CNAs in iPSC clones derived from Bak −/– ; Bax −/– MEFs compared with those derived from WT MEFs ( Figures 4 C, 4D, S3 A, and S3B). Although this method is not sensitive enough to detect single-nucleotide aberrations that may occur during reprogramming, these results are consistent with reports that the process of reprogramming is not inherently mutagenic ( Young et al., 2012 ) and that embryonic stem cells lacking BAK and BAX maintain a normal karyotype ( Wang et al., 2015 ). In contrast, iPSC clones derived from p53 -deficient MEFs exhibited a significantly higher number of CNAs compared with the Bak −/– ; Bax −/– and WT groups ( Figures 4 C, 4D, and S3 C).…”
Section: Resultssupporting
confidence: 88%
“… 73 Furthermore, it has recently been suggested that ESC differentiation is efficiently maintained by eliminating those cells that are slow to exit pluripotency, implicating a novel role for the apoptotic signaling pathway. 81 Therefore, we propose that the functions of the principal GECN in ESCs should play a significant role in determining the ESCs mechanisms of stemness.…”
Section: Resultsmentioning
confidence: 99%
“…Fas binds to FasL to form a death-induced compound. This compound activates Caspase 8 that induces Caspase 3 production and activates death receptor apoptosis pathway [ 8 ]. At present, it is believed that COX-2 plays an important role in regulating the expression of Fas receptor in pulmonary fibroblasts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%